2022
DOI: 10.3390/jpm12060855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Personalized Serum IgG Subclass Ratios for the Differentiation of IgG4-Related Sclerosing Cholangitis (IgG4-SC) from Primary Sclerosing Cholangitis (PSC) and Cholangiocarcinoma (CCA)

Abstract: Background: The differential diagnosis of immunoglobulin G4-sclerosing cholangitis (IgG4-SC) from primary sclerosing cholangitis (PSC) or cholangiocarcinoma (CCA) is important. In this study, we aimed to find the best combinations of serum IgG subclasses and IgG4 levels for differentiating IgG4-SC from PSC or CCA. Methods: In total, 31 patients with IgG4-SC, 27 patients with PSC, and 40 patients with CCA were enrolled from 2003 to 2017 at a single tertiary referral center. We retrospectively assessed the IgG4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previously published studies on PSC and high IgG4 levels have been underpowered to assess the risk of malignancy in this specific cohort of patients [ 2 ]. Recent findings indicate that measurement of serum IgG4/IgG1 or IgG4/(IgG1+IgG3) levels may help to differentiate IgG4-related cholangitis from PSC [ 18 ]. In the same study, IgG4 alone was shown to be the most accurate serologic marker for the differentiation of IgG4-related cholangitis from cholangiocarcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published studies on PSC and high IgG4 levels have been underpowered to assess the risk of malignancy in this specific cohort of patients [ 2 ]. Recent findings indicate that measurement of serum IgG4/IgG1 or IgG4/(IgG1+IgG3) levels may help to differentiate IgG4-related cholangitis from PSC [ 18 ]. In the same study, IgG4 alone was shown to be the most accurate serologic marker for the differentiation of IgG4-related cholangitis from cholangiocarcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that measurement of serum IgG4/IgG1 or IgG4/(IgG1+IgG3) levels may help to differentiate IgG4-related cholangitis from PSC [ 18 ]. In the same study, IgG4 alone was shown to be the most accurate serologic marker for the differentiation of IgG4-related cholangitis from cholangiocarcinoma [ 18 ]. IgG levels in our study were not associated with the development of cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-SC is also a common complication of multifocal biliary strictures and IBD, and therefore, it may be misdiagnosed in some cases ( 161 ). In contrast to PSC, IgG4-SC is a multisystem fibroinflammatory disease that is defined by substantial lymphoplasmacytic infiltration of IgG4-positive cells and increased serum levels of IgG4 ( 162 ). Both the serum IgG4/IgG1 ratio and IgG4/IgG RNA ratio can be used to differentiate between the two conditions ( 163 ).…”
Section: Inflammasomes and Pyroptosis In Aildsmentioning
confidence: 99%
“…serum levels of IgG4 (162). Both the serum IgG4/IgG1 ratio and IgG4/IgG RNA ratio can be used to differentiate between the two conditions (163).…”
Section: Inflammasomes and Pyroptosis In Igg4-scmentioning
confidence: 99%